Contested, violated but persistent: presidential term limits in Latin America and sub-saharan Africa. Issue 1 (2nd January 2022) - Heyl, Charlotte; Llanos, Mariana
ABSTRACT: Presidential term limits have been a crucial institutional feature of the third wave of democratization. They are meant to safeguard democracy by promoting alternation in office and preventing the personalization of power. However, since the 1990s term limits have been subject to frequent contestation by incumbents. This process has often been considered a sign of autocratization because it involves the weakening of other constitutional constraints, such as courts and legislatures. Latin America and sub-Saharan Africa are focal points of these trends, despite their different histories of presidentialism and diverging types of term-limit rules. Term-limit contestations have attracted the attention of scholars working with a global perspective as well as with a regional or country-specific one too. In this article, we argue that bringing together the regional scholarship on Latin America and sub-Saharan Africa can generate new both empirical and theoretical insights. We further present our findings on institutionalization, the power of precedence, incumbent-centred strategies and approaches to protect presidential term limits. We also show that despite frequent reforms, term-limit rules have persisted until today in the majority of constitutions found in the two regions.